Corrective feedback in dialogue-based computer assisted language learning - Basiron, Halizah (2008)
Computer assisted language learning (CALL) systems are used by people to learn a language. CALL systems have provided a number of advantages for language learning such as their ability to provide consistent and flexible corrective feedback during the learning process. This feedback is expressed as information about what is ungrammatical or unacceptable in a target language. This paper presents a literature study on the field of corrective feedback and CALL and describes the future plan for my PhD research.